2021
DOI: 10.1007/s00198-021-06025-y
|View full text |Cite
|
Sign up to set email alerts
|

Bone turnover and mineral metabolism in adult patients with hypophosphatasia treated with asfotase alfa

Abstract: There is limited understanding of how asfotase alfa affects mineral metabolism and bone turnover in adults with pediatric-onset hypophosphatasia. This study showed that adults with hypophosphatasia treated with asfotase alfa experienced significant changes in biochemical markers of bone and mineral metabolism, possibly reflecting enhanced bone remodeling of previously osteomalacic bone. Introduction Hypophosphatasia (HPP), due to a tissue nonspecific alkaline phosphatase (TNSALP) deficiency, can cause impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…Certainly, the osteoblast production of alkaline phosphatase is compromised and it would be of interest to know what serum calcium and serum PTH levels are in the mutant mice. Adult humans with hypophosphatasia have levels of PTH 1-84 levels in the normal range [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, the osteoblast production of alkaline phosphatase is compromised and it would be of interest to know what serum calcium and serum PTH levels are in the mutant mice. Adult humans with hypophosphatasia have levels of PTH 1-84 levels in the normal range [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the anabolic actions of PTH which are particularly prominent in growing mice may be restrained by alkaline phosphatase under normal conditions. Interestingly, a recent study of asfotase alfa enzyme replacement (Strensiq®) in human adults with hypophosphatasia found enzyme replacement therapy led to transient increases in PTH 1-84 levels [ 33 ]. Anabolic PTH is well known to increase P1NP levels and is a marker of the effective increase in bone formation evoked by PTH.…”
Section: Discussionmentioning
confidence: 99%
“…Asfotase alfa also seems to be beneficial for adult patients with pediatric-onset HPP, improving the biochemical characteristics of the disease: it increases TNSALP activity and lowers both PLP and PPi levels [67][68][69], with no significant difference between the ALPL variant states [70]. When a group of adolescents and adults with childhood-onset HPP, treated with asfotase alfa, was compared to an untreated control group, after 6 months of therapy, there was found a higher TNSALP activity, lower PLP and PPi levels and significant improvement in the 6-minute-walk test [67].…”
Section: Asfotase Alfa: Recombinant Enzyme Replacement Therapy In Hppmentioning
confidence: 99%
“…Lumbar spine BMD T-scores continued to increase throughout the follow up. They concluded that asfotase alfa mediates bone mineralization and bone turnover on previously inaccessible bone [69] (▶Fig. 3).…”
Section: Asfotase Alfa: Recombinant Enzyme Replacement Therapy In Hppmentioning
confidence: 99%
“…Similarly favorable results were reported in several case reports in adults with HPP [ 102 , 103 , 104 , 105 , 106 ]. In addition, Seefried et al [ 107 ] reported the 24-month effect of asfotase alfa on bone turnover markers and BMD in 21 adults with paediatric-onset HPP. Serum osteocalcin, procollagen-1 N-terminal peptide and PTH increased at 3 and 6 months and returned to baseline at 12 months, while tartrate-resistant acid phosphatase 5b increased at 3 months and returned to baseline thereafter.…”
Section: Managementmentioning
confidence: 99%